2018
DOI: 10.1021/acsinfecdis.7b00085
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Molecules Competitively Interfere with Cholera Toxin Binding to Host Cells

Abstract: Cholera toxin (CT) enters host intestinal epithelia cells, and its retrograde transport to the cytosol results in the massive loss of fluids and electrolytes associated with severe dehydration. To initiate this intoxication process, the B subunit of CT (CTB) first binds to a cell surface receptor displayed on the apical surface of the intestinal epithelia. While the monosialoganglioside GM1 is widely accepted to be the sole receptor for CT, intestinal epithelial cell lines also utilize fucosylated glycan epito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 56 publications
8
61
0
1
Order By: Relevance
“…Moreover, SPR experiments with toxin variants confirmed that disruption of the secondary binding site, but not the primary binding site, lowered the affinity to Le x (Figure 4, Table 2). We also found that Le x bound more weakly to CTB than Le y or A-Le y , which is in good agreement with inhibitor studies identifying Le y as the most potent small-molecule inhibitor of CTB 33 . The binding mode of Le x is highly similar to that of Le y tetraose and A-Le y pentaose 19 , which both feature an additional fucose residue (Figure 2 c).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, SPR experiments with toxin variants confirmed that disruption of the secondary binding site, but not the primary binding site, lowered the affinity to Le x (Figure 4, Table 2). We also found that Le x bound more weakly to CTB than Le y or A-Le y , which is in good agreement with inhibitor studies identifying Le y as the most potent small-molecule inhibitor of CTB 33 . The binding mode of Le x is highly similar to that of Le y tetraose and A-Le y pentaose 19 , which both feature an additional fucose residue (Figure 2 c).…”
Section: Discussionsupporting
confidence: 88%
“…Addition of a methyl group to OH1, locking the anomeric hydroxyl group in the P-configuration, resulted in less efficient CTB binding compared to L -fucose or α-locked fucose. Finally, the SAR study showed increased binding of α1,2 linked fucose compared to α1,3 linked fucose 33 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations